1993
DOI: 10.1128/mcb.13.10.6558
|View full text |Cite
|
Sign up to set email alerts
|

A family of human phosphodiesterases homologous to the dunce learning and memory gene product of Drosophila melanogaster are potential targets for antidepressant drugs.

Abstract: We have isolated cDNAs for four human genes (DPDE1 through DPDE4) closely related to the dnc learning and memory locus ofDrosophila melanogaster. The deduced amino acid sequences of the Drosophila and human proteins have considerable homology, extending beyond the putative catalytic region to include two novel, highly conserved, upstream conserved regions (UCR1 and UCR2). The upstream conserved regions are located in the amino-terminal regions of the proteins and appear to be unique to these genes. Polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
279
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 270 publications
(289 citation statements)
references
References 15 publications
9
279
0
1
Order By: Relevance
“…The human counterpart of this latter form has been described by Bolger et al [22]. A fourth variant (PDE4D4) was also detected in human [22] and rat (Vicini, E. and Conti, M., unpublished results), suggesting the presence of a third, distinct promoter. Hormones control the activation and expression of the PDE4D variants through an increase in intracellular cAMP levels.…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…The human counterpart of this latter form has been described by Bolger et al [22]. A fourth variant (PDE4D4) was also detected in human [22] and rat (Vicini, E. and Conti, M., unpublished results), suggesting the presence of a third, distinct promoter. Hormones control the activation and expression of the PDE4D variants through an increase in intracellular cAMP levels.…”
Section: Introductionmentioning
confidence: 62%
“…Another variant, rat PDE4D3, detected in the brain and FRTL-5 cells, is derived from the activity of a different promoter and the transcription of upstream exons [27]. The human counterpart of this latter form has been described by Bolger et al [22]. A fourth variant (PDE4D4) was also detected in human [22] and rat (Vicini, E. and Conti, M., unpublished results), suggesting the presence of a third, distinct promoter.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…PDE4B has five splice variants (PDE4B1, 4B2, 4B3, 4B4, and 4B5; Bolger et al, 1993Bolger et al, , 1994Cheung et al, 2007;Huston et al, 1997;Shepherd et al, 2003). While the roles of these variants are still not known, recent studies using mice deficient in PDE4B have shown that this subfamily plays a complementary role in the control of neutrophil function (Ariga et al, 2004) and is required for antipsychotic effects of rolipram (Siuciak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%